Growth of 2D nanoflakes from 1D long leaf arrays: Electrochemical influence of copper and nickel co-substituted cobalt oxide. (December 2020) - Hussain, Iftikhar; Mohapatra, Debananda; Dhakal, Ganesh; Lamiel, Charmaine; Mohamed, Saad Gomaa; Sayed, Mostafa Saad; Lee, Yong Rok; Lee, Jintae; Lee, Moonyong; Shim, Jae-Jin
Highlights: 2D Cu-Ni-Co ternary oxide nanoflakes were grown from 1D long leaf arrays. The Cu-Ni-Co oxide electrode showed a high specific capacity 1046 C g − 1 at 1 A g − 1 . Cu-Ni-Co oxide showed higher capacity and rate capability than NiCo2 O4 and Co3 O4. The HSC device delivered specific energy 51 W h kg −1 at a specific power 764 W kg −1 . The HSC device illuminated 52 parallel red LEDs for approximately 266 s. Abstract: 2D Cu-Ni-Co ternary oxide nanoflakes from 1D long leaf arrays were prepared using a simple, cost-effective, environmentally friendly hydrothermal approach, followed by heat treatment in air, and their supercapacitive performance was investigated. The binder-free 2D Cu-Ni-Co oxide nanoflakes electrode possessed an outstanding specific capacitance of 2615 F g − 1 (1046 C g − 1 ) at a current density of 1 A g − 1 as well as excellent rate capability and high capacitance retention of 88% at a high current density of 10 A g − 1 in a three-electrode configuration. A hybrid supercapacitor device exhibited a high specific capacity of 185 C g − 1 at 1 A g − 1 and high capacitance retention of 90.2% after 10, 000 cycles. Additionally, the hybrid supercapacitor device delivered high specific energy of 51 Wh kg −1 at a specific power of 764 W kg −1 . The attractive electrochemical performance of Cu-Ni-Co oxide makes this a promising electrode material for practical supercapacitor applications. Graphical abstract: Image, graphical abstract